2016
DOI: 10.1016/j.oraloncology.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of palbociclib, a selective cyclin dependent kinase 4/6 inhibitor, in combination with cetuximab in patients with recurrent/metastatic head and neck squamous cell carcinoma

Abstract: Objectives To test the safety of the CDK4/6 inhibitor palbociclib with cetuximab in patients with recurrent/metastatic head and neck squamous cell carcinoma(HNSCC). Materials and Methods A phase I trial using 3+3 design was performed to determine the dose limiting toxicity(DLT) and maximum tolerated dose(MTD) of palbociclib with standard dose weekly cetuximab. Palbociclib was administered orally days 1-21 every 28 days:dose level 1(100 mg/d) and 2(125 mg/d;approved monotherapy dose). Pharmacokinetic assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…[5][6][7][8][9][10][11] We analyzed the combinatorial effects of palbociclib with the commonly used chemotherapy agents against CRC, as a prelude to possible translation. Chou-Talalay analysis revealed that palbociclib can synergize with a variety of chemotherapies under hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11] We analyzed the combinatorial effects of palbociclib with the commonly used chemotherapy agents against CRC, as a prelude to possible translation. Chou-Talalay analysis revealed that palbociclib can synergize with a variety of chemotherapies under hypoxia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Our assessment of IC50 values indicated that the CDK4/6 inhibitor palbociclib reduces the viability of CRC cells regardless of the presence of hypoxia (Fig 1). 5-FU, oxaliplatin and irinotecan are the backbone standard chemotherapy agents used to treat patients with advanced CRC.…”
Section: Palbociclib Synergizes With Cpt11 and Reduces The Viability mentioning
confidence: 91%
See 1 more Smart Citation
“…In head and neck cancer, palbociclib has been tested in combination with cetuximab in a phase I trial and was well tolerated. Some preliminary efficacy was observed, and a phase II study is currently enrolling patients (NCT02499120) [22]. …”
Section: Targeted Therapies In Head and Neck Cancermentioning
confidence: 99%
“…Due to the limited number of patients, neither CCND1 nor Rb expression could be statistically evaluated with regard to tumor response, and the data were unclear for p16 (CDKN2A) expression [22]. In breast cancer, neither PIK3CA mutation status in a phase III trial nor CCND1 amplification, p16 expression, or Rb localization in a phase II trial were associated with response [21,54].…”
Section: Predictive Biomarkersmentioning
confidence: 99%